Development of low-cost rolling base isolation system for seismic protection of rubble stone masonry buildings in Himalayan Mountain range - Takagi, Jiro; Masui, Takeshi; Araki, Yoshikazu; Ikago, Kohju; Pareek, Sanjay; Lee, Sanghun; Suzuki, Yusuke; Enokida, Ryuta; Guo, Jia; Shrestha, Kshitij C.; Fukuda, Iori; Miyagawa, Hayato (Frontiers in Built Environment, 2024)
A low-cost rolling base isolation system (RBIS) for rubble stone masonry buildings in the Himalayan mountain range was presented and the feasibility of RBIS in the initial conditions installed in the buildings were evaluated in experiments and simple numerical simulations. The base isolation layer is composed of styrofoam, concrete slab and cast-iron balls. The styrofoam and concrete slab are the upper and lower elements of the isolation layer. The styrofoam boards are used for the embedment of the cast-iron balls and form panels for the casting concrete of the tie beams above the isolation layer. In the case of large earthquakes, these balls roll and horizontally squeeze into the styrofoam boards. The proposed RBIS satisfies two issues for the base isolation system in rubble stone masonry buildings in the Himalayan Mountain range; i.e. (i) use of locally available materials in the isolation layer and (ii) simple construction procedure of the isolation layer by local workers. The quasi-static cyclic loading experiments were conducted. The rolling coefficients of the RBIS were 0.06–0.14. Shaking table experiments were also conducted. It was found that the recorded maximum accelerations are approximately 0.2g. The restoring force characteristics of RBIS in the shaking table experiment were created and the behavior of the experiment was simulated by the response history analyses (RHAs). The behavior of the rubble stone masonry building associated with RBIS under large earthquakes was also evaluated in RHAs. Assuming that the traditional masonry buildings can resist the earthquake ground motions with a PGA under 0.15g, the buildings installed with RBIS can resist the ground motions with a PGA under 0.5g.